Concert of Beethoven and Schubert works by Johannes Martinus Messchart and Julius Röntgen, Amsterdam (Netherlands; Stumpff & Koning; Amsterdam, 2020)
Program of a performance by Joh. Messchaert (baritone) and Julius Röntgen (piano) of An die ferne Geliebte, op. 98, and Schubert's Winterreise, and of Röntgen's performance of the Beethoven Piano Sonatas op. 31/2 and op. 109. Includes texts of the vocal works in German.